2016
DOI: 10.1111/twec.12473
|View full text |Cite
|
Sign up to set email alerts
|

Narrow and Broad Perspectives on Trade Policy and Trade Costs: How to Facilitate Trade in Madagascar

Abstract: Madagascar is a high trade cost and relatively closed economy. The WTO's latest Trade Policy Review (TPR) for the country, like all TPRs, concentrates on border sources of trade costs, those induced by trade policy instruments such as tariffs or implicit taxes imposed by slow and costly customs procedures or trade documentation requirements. This narrow focus for trade policy and facilitation misses the substantive within‐and‐beyond‐the‐border sources of trade costs experienced by traders in a country like Mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…While these WTO rules contribute to reducing trade costs and ensuring the stability and predictability of the trading environment, the facilitation of trade, that is, the reduction in the overall trade costs, requires lowering both border and non-border sources of trade costs (e.g., Ali and Milner 2016). The concept of "trade costs" is defined in a broad sense by Anderson and van Wincoop (2004, p. 691) as encompassing all costs incurred in delivering a good to a final user other than the marginal cost of producing the good itself.…”
Section: Introductionmentioning
confidence: 99%
“…While these WTO rules contribute to reducing trade costs and ensuring the stability and predictability of the trading environment, the facilitation of trade, that is, the reduction in the overall trade costs, requires lowering both border and non-border sources of trade costs (e.g., Ali and Milner 2016). The concept of "trade costs" is defined in a broad sense by Anderson and van Wincoop (2004, p. 691) as encompassing all costs incurred in delivering a good to a final user other than the marginal cost of producing the good itself.…”
Section: Introductionmentioning
confidence: 99%
“…While these WTO rules contribute to reducing trade costs, and ensuring the stability and predictability of the trading environment, the facilitation of trade, that is, the reduction of the overall trade costs, requires lowering both border and non-border sources of trade costs (e.g., Ali and Milner, 2016). The concept of "trade costs" is de ned in a broad sense by Anderson and van Wincoop (2004: p691) as encompassing all costs incurred in getting a good to a nal user other than the marginal cost of producing the good itself: transportation costs (both freight costs and time costs), policy barriers (tariffs and nontariff barriers), information costs, contract enforcement costs, costs associated with the use of different currencies, legal and regulatory costs, and local distribution costs (wholesale and retail).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, trade facilitation entails reducing both border-induced trade costs (e.g., tariffs, and other explicit and implicit border taxes, such as those associated with stringent and costly customs procedures) and non-border sources of trade costs such as inadequate domestic transport infrastructure, ine cient domestic transport and other services (e.g., port services) and the additional costs (related to communication, information, etc.) involved in conducting business across national frontiers (e.g., Ali and Milner, 2016). The literature has shown that in parallel to the fall in import tariff rates, non-border trade costs have been on rise, and generate massive trade costs (e.g., Arvis et The Trade Facilitation Agreement (TFA) adopted by WTO members at the Bali Ministerial Conference held in December 2013 has been instrumental in promoting the stability and predictability of the trading environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that this definition of 'tax transition reform' does not imply that the optimal reform of domestic taxation (through tax rates and tax bases design) in developing countries should be the same as that of developed countries. We are mainly interested in the shifts in the tax revenue structure in favour of domestic tax revenue, regardless of the nature of domestic taxation reform in developing countries.8 See for example,Anderson and Marcouiller (2002);Ali and Milner (2016);Arvis et al (2010);Diakantoni et al (2017);Hoekman and Nicita (2011);Hoekman and Shepherd (2015);Jacks et al (2008Jacks et al ( , 2011;Novy (2013);Shepherd (2022) andWTO (2021). A literature review on the trade effects of trade facilitation could be found inBeverelli et al (2015).…”
mentioning
confidence: 99%